Perancangan Sistem Informasi Monitoring Kegiatan Praktek Kerja Industri SMK Negeri 2 Kota Solok Berbasis Web - Ridwan, Ridwan (Greenation Publisher & Yayasan Global Resarch National, 2023)
In the design of an information system, all data relating to monitoring activities for industrial work practices at SMK Negeri 2 Kota Solok is stored in a file warehouse called a database. In designing a database or database, several stages of design are needed. To produce a good and correct database, it is necessary to carry out the stages of system design, such as context diagrams, DFD, ERD, etc., the aim is to produce good data input. The database used for making the Information System for monitoring Industrial Work Practices at SMK Negeri 2 Solok City uses MySQL. And in making the display (interface) using PHP, HTML, CSS and Javascript. Utilization of online information technology helps in monitoring student activities during Internships, both student reports themselves, industry and tutors themselves, meetings, attendance, schedules, facilities can be done online.